In Vitro Antitumor Activity of Aloperine on Human Thyroid Cancer Cells through Caspase-Dependent Apoptosis - Lee, Ying-Ray; Chen, Shu-Hsin; Lin, Ching-Yen; Chao, Wen-Ying; Lim, Yun-Ping; Yu, Hui-I; Lu, Chieh-Hsiang (International journal of molecular sciences, 2018)
The global incidence of thyroid cancer, one of the most common endocrine malignancies, is especially high among women. Although most patients with thyroid cancers exhibit a good prognosis with standard treatment, there are no effective therapies for patients with anaplastic thyroid cancers or cancers that have reached an advanced or recurrent level. Therefore, it is important to develop highly effective compounds for treating such patients. Aloperine, a natural compound isolated from Sophora alopecuroides, has been reported to possess antioxidant, anti-inflammatory, anti-neuronal injury, anti-renal injury, antitumor, anti-allergic, and antiviral properties. In this study, we show that aloperine can inhibit cell growth in human anaplastic thyroid cancers and multidrug-resistant papillary thyroid cancers. Moreover, it could suppress in vitro tumorigenesis and promote cellular apoptosis. Further analysis demonstrated the involvement of caspase-dependent apoptosis, including intrinsic and/or extrinsic pathways, in aloperine-induced cellular apoptosis. However, cell cycle regulation was not detected with aloperine treatment. This study suggests the potential therapeutic use of aloperine in human anaplastic thyroid cancers and multidrug-resistant papillary thyroid cancers.